HARUSKAH AKU TETAP BERTAHAN? STUDI FENOMENOLOGI TERKAIT KECENDERUNGAN TURNOVER INTENTION PADA GENERASI Z - I Putu Dharmawan Pradhana; Luh Putu Sri Devi Mahayuni; Putu Yoga Purnama Wijaya; Putu Adi Saskara Putra; Ni Ketut Arniti (Juremi: Jurnal Riset Ekonomi, 2024)
The high turnover propensity in the workplace is a characteristic of Generation Z, born between 1995 and 2010. Since this generation makes up about 48% of Bali’s working population, businesses must create efficient human resource management plans. A notable characteristic of Generation Z is their dislike of stressful work settings, frequently resulting in them changing jobs. This study aims to investigate how Generation Z workers manage stress at work and whether they plan to quit. Purposive sampling is used in this qualitative study to choose three primary informants—Gen Z employees who are stressed out and considering changing jobs—as well as three supporting informants (coworkers) and one psychological practitioner. NVivo 14 software was used to analyse the data gathered from observations, interviews, and documentation at three different Denpasar City and Badung Regency businesses. The results show that although the primary informants indicated a wish to switch jobs because of stress, they chose to stay with their existing employers, using various coping mechanisms to lessen stress and decrease plans to leave. The investigation also discovered particular behavioural shifts in the informants. One of its limitations is that it only looks at Generation Z singles, indicating that more research is necessary to include a broader range of people. By addressing their concerns, this study helps organisations retain Generation Z and advances our understanding of their workplace dynamics